A Comparative Study of Three Methods for the Visualization of von Willebrand Factor (vWF) Multimers - Ledford, M R; Kent, J W; Civantos, F (Thrombosis and Haemostasis, 1990)
This study was performed to compare three visualization methods for the detection of vWF multimers: autoradiography (125I), electroblot with a horseradish peroxidase system (BLOT-HRP), and an avidin-biotin peroxidase system (AV-BIO). Each method was evaluated according to: 1) ability to visually detect bands and subbands thereby identifying von Willebrand’s disease (vWD) subtypes and normals, 2) reagent availability, 3) cost, and 4) time requirements. Additionally, resolvability was evaluated utilizing low, intermediate, and high resolution gels prepared with both low and high gelling temperature agaroses with subsequent visualization by the three detecting systems.With intermediate resolution gels, our results showed that all three visualization methods could discern pathologic patterns from normal. In addition, the avidin-biotin peroxidase system demonstrated the best band discreteness with low resolution gels used to detect unusually high molecular weight multimers. With high resolution gels used for subtyping type II vWD, we found the internal band structure was best demonstrated using LGT agarose and the electroblot horseradish peroxidase system.